STRATEGI KOMUNIKASI HUMAS POLRESTA SURAKARTA DALAM SOSIALISASI APLIKASI SIOLOS - Yudha, Yudha Prasetyo; Wisudawanto, Rahmat; Putri, Sofia Ningsih Rahayu (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2023)
SIOLOS application stands for Sistem Operasi Layanan Online. The SIOLOS application itself is an applicationreleased by the Surakarta Police which is useful for improving information services to the public, especiallyonline services. The function of this application includes various uses, namely there are many featuressuch as procedures for making a SIM, SKCK, and so on.The public relations of Polresta Surakarta used socialmedia Instagram with the account name @polrestasurakarta. The study aimed to explain the public relationsstrategy of Polresta Surakarta in disseminating the SIOLOS application. This research used a descriptivequalitative research method. Methods of collecting data used interviews and documentation. The results showed thatthe Polresta Surakarta Public Relations strategy in socializing the SIOLOS application, namely publication,event, news, corporate identity, community involvement, lobbying and negotiation, and corporate socialresponsibility. The public relations of Polresta Surakarta were quite effective in conducting its socializationbecause it used Instagram social media, which has about 65 thousand followers and is widely accessed by thepublic.